Collocating peace - Michela Montevecchi (Journal of Modern Languages)
What is peace? How do we experience and interpret it? How true the proverb is: if you want peace, you must prepare for war? In addition, what are its cognitive, socio-cultural and linguistic implications? How deeply are we culturally and linguistically imbued in, or conditioned by, metaphors in our interpretation of peace? This investigation focuses on some representative noun+noun sequences in referring to peace, from a socio-linguistic perspective and a critical linguistic approach. As Biber (2002) explains, â€œnoun+noun sequences contain only content words that present information densely and are used to express a bewildering array of logical relations with implicit meaning that the reader must infer from the intended logical relationshipâ€. The intended logical relationships represent the conceptual interpretation of cognitively meaningful content words, which, in the end, become the established and consolidated lexical patterns of peopleâ€Ÿs common sense, social practice and ideology: the ideology of war.